Malay Islamic Branding Consistency: Building A University Identity - Fera Indasari; Sepriadi Saputra; Ida Anggriani; Nur Syafitri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The State Islamic University in Palembang City is an institution that must establish a credible identity and strong reputation to attract high-quality students. To achieve this, it is essential to maintain consistent branding, with a focus on a Malay-Islamic identity. This study, titled Consistency of Malay-Islamic Branding: Building University Identity, aims to explore how consistent branding efforts can help build the university's identity. The theoretical framework for this study is based on branding consistency, derived from Fritz Heider's Balance Theory (1946). The study employs a qualitative approach, utilizing in-depth interviews. The findings reveal several key challenges: inconsistent branding initiatives, limited resources and organizational structure, a restricted role of public relations in branding, suboptimal engagement of lecturers as brand ambassadors, and a lack of structured evaluations for assessing branding consistency at the State Islamic University in Palembang City.